Leveraging Social Protection Policies and Programs for Promoting Healthy Diets and Improved Nutrition: The Global Perspective - Ecker, Olivier (2018)
as part of the IFPRI Session – “Leveraging Social Protection Policies and Programs for Promoting Healthy Diets and Improving Nutrition”.